MOTIVASI SISWA PUTRA KELAS XI DALAM MENGIKUTI PROSES PEMBELAJARAN BOLA VOLI DI SMAIT MUTIARA DURI - Rahmatullah, M Imam; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:The problem in this research is the lack of motivation of Class XI male students in the volleyball learning process in SMAIT Mutiara Duri. The purpose is to determine the percentage of student motivation in the volleyball learning process. The samples were obtained by using slovin formula by total 62 male students in SMAIT Mutiara Duri. The method used in this research is descriptive analysis method percentage.Technique that is used in collecting data is questioner and analyzing the data in report and related proves.There are four indicators: (1) Passion and interest to succeed by 76%,(2) Stimulation and need to learn by 63,6 %, (3) Reward in learning 84,7 %,(4) Facility and conducive learning environment by 88,2%. Therefore the overall result percentage of Class XI male student motivation in the volleyball learning process is equal to 89.7% in good category. Keywords: Motivation,stimulus,student